Analysis of Heavy Metal Contamination in Industrial Wastewater along the Biratnagar– Duhabi Industrial Corridor: Their Environmental Impacts - Shah, Sujit Kumar; Adhikari, Man Bahadur; Bhattarai, Ajaya (Tribhuvan University Journal, 2024)
The generation and collection of heavy metals in wastewater are increasing due to rapid overpopulation, urbanization, and industrialization. Thus, it is critical to manage and treat the wastewater released from industries, cities, and agricultural sites, before discharging them into the drainage system. This research paper investigated the contamination of heavy metals in industrial effluent in the Biratnagar-Duhabi corridor of Kosi province, Nepal. Three types of industrial effluents, namely, the iron processing industry (IR), battery industry (BT), and leather processing industry (LT) are chosen. pH, biological oxygen demand (BOD), chemical oxygen demand (COD), and selected heavy metals such as Zinc (Zn), Lead (Pb), Cadmium (Cd), Chromium(Cr), Nickel (Ni), and Cobalt (Co) are investigated in the samples of effluents. pH was found in the range of 1.86 to 11.63. BOD and COD data showed that the samples are heavily polluted from organic and other chemical pollutants. One sample from IR has high levels of Zn concentrations. Samples from BT were found to have high levels of Pb concentration.